"They think you're trying to get the drug": Qualitative investigation of chronic pain patients' health care experiences during the opioid overdose epidemic in Canada. Issue 1 (1st January 2021) - Dassieu, Lise; Heino, Angela; Develay, Élise; Kaboré, Jean-Luc; Pagé, M. Gabrielle; Moor, Gregg; Hudspith, Maria; Choinière, Manon
ABSTRACT: Background : The opioid overdose epidemic has led health care providers to increased vigilance for opioid-related risks in the treatment of chronic non-cancer pain (CNCP). Media have conveyed stigmatizing representations of opioid analgesics. Aims: This study aimed to understand how the opioid overdose epidemic has impacted health care experiences among people living with CNCP in two Canadian provinces (British Columbia, Quebec). Methods: This qualitative study proceeded through 22 semi-structured interviews conducted in 2019. Participants were recruited from a cross-sectional survey examining the effects of the opioid overdose epidemic on individuals with CNCP. We collected in-depth narratives that we analyzed using a thematic framework. The sample included 12 women and 10 men aged 20 to 70 years, with 11 from each province. Results: Several participants described increased difficulty in accessing medical services for pain since the onset of the opioid overdose epidemic. They reported that some physicians urged them to taper opioids regardless of their pain severity and functional limitations. Some participants reported facing discrimination and care denials as they were labeled "drug-seeking, " especially in hospital. Depending on their educational resources, they were unequally able to counter providers' stigmatizing behaviors. However, participants described empathetic relationships with providers with whom they had a long-term relationship. Some participants drew distinctions between themselves and the stigmatized status of "addict" in ways that reinforced stigma toward people who are dependent on opioids. Conclusions: Health policies and provider education programs aimed at reducing opioid-related stigma are needed to counter detrimental consequences of the opioid overdose epidemic for people living with CNCP.